Etnomatematika Pada Bentuk Jajajan Pasar di Pasar Kleco Surakarta - Herawati, Ratna; Sumboro, Budhi (JURNAL SINEKTIK, 2024)
Surakarta is a city that is still closely related to tradition. Traditional foods such as market snacks are one of the requirements that are usually used in the procession. Processions such as gunungan, apeman, wedding processions, dead people, and also sekatenan are inseparable from traditional food elements. This study aims to discover the geometric shapes in various market snacks and the related mathematical elements. The researcher used the ethnomathematics approach to explore the various shapes of market snacks based on the elements of flat and spatial shapes both flat and curved sides in School material. This research is in the form of descriptive qualitative. The data collection process was carried out by literature review, field studies, and interviews with several related sources. The mathematical geometric elements found in this study are quite a lot including the shape of the flat square, rectangle, and circle, while the shape of the space includes the shape of the cube, beam, ball, cylinder, and cone. The results of this study can provide benefits for contextual learning of the use of mathematical concepts in everyday life.